Pre-service EFL Teachers’ Perceptions on the Use of ESP Material Development in Their Teaching Practice - Artiningsih, Hana Dewanti (Universitas Negeri Surabaya, 2023)
This study aims to find out the pre-service EFL teachers' perceptions of the role of the ESP Material Development course in their teaching practice activities at Vocational Highschool (VHS). This present study takes place at a state university in Surabaya, especially at an English language education study program. This study uses qualitative research, especially case study. The data will be analyzed by giving semi-structured interviews and reviewing documents to the English education students of 2019 cohort at the University State at Sura Bayaya English education student of 2019 who had taken the English language Education Study Program (ESP) Material Development Course and had done their teaching practices at VHS. The results of the interview showed that the Pre-Service EFL teacher think that ESP Materials Development are important for their teaching in VHS, and one of the challenges they face in applying their knowledge to meet their students' needs is the varying English language proficiency levels among their students. Based on the findings, it can be concluded that the preservative teachers perception of the use of ESP material development in teaching practice is important. It is necessary for the teachers to be equipped with courses related to the preparation of material for teaching English by the majors or specializations of each VHS student.